Mycorrhiza Arbuscular's Morpho-Species Identification in The Post- Nickel Mining Soil - Abdullah, Sofyan; Jayadi, Muh.; Neswati, Risma; Ardiansyah, Andri; Harri, Erlin; Adzima, Ahmad Fauzan (Universitas Hasanuddin, 2024)
Using biological agent microorganisms such as Arbuscular Vesicular Mycorrhiza (AVM) is needed to improve post-mining soil fertility. This research aimed to explore and identify morpho species of AVM in the post-nickel mining areas Soil samples were taken from the tree rhizosphere at each representative point. The soil samples have been isolated using Brundrett's method of wet sieving and decanting; AVM spore density is determined for each 20 g soil sample; and spores are grouped based on morphological traits up to the morphogenic stage of the species. The results showed that there are four mycorrhizal species found in the rhizosphere of plants in the nickel post-mining soil of PT Vale Indonesia Tbk., namely Gigaspora sp, Acaulospora sp, Glomus sp, and Scutellospora sp. Gigaspora sp, Acaulospora sp, Glomus sp, and Scutellospora sp obtained 18, 8, 8, and 7 morpho species, respectively. The highest spore density is 34 spores of Gigaspora sp4 found in the rhizosphere of Casuarina rumphiana, 57 spores of Acaulospora sp1 in the rhizosphere of Macaranga gigantea, two spores of Glomus sp1, sp2, and sp6 each as many as two spores per 20 g of soil in rhizosphere of Enterolobium cyclocarpum, Dillenia serrata, Maesopsis eminii, 11 spores of Scutellospora sp6 in the Shizigium sp rhizosphere. One finding revealed that Gigaspora and Acaulospora predominated in the rhizosphere over other mycorrhizas. The results of this AVM identification will be the basis for the mass propagation of local AVM for broader use in the post-nickel mining land area in Sorowako. Widespread use of AVM is a form of post-nickel mining land management based on local resource potential, particularly the dominant trees rhizosphere and the most commonly found AVM types. This proves that AVM can colonize plant roots in this nickel post-mining soil and potentially be mass-propagated, especially species.